Tinjauan terhadap Metode Empirisme dan Rasionalisme - Al Munir, M. Ied (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Rasionalism and empiricism conceptions have so many weakness to use as a method to get knowledge. Therefore, it is a much need another method that can be expected to revise those weakness. This method is a combination between the Rasionalism conceptions and the empiricism conceptions. Afterwards, it is known as scientific method.